ANALISIS KINERJA KEUANGAN PT. BPD NTB PERIODE 2012 - 2017 - I ketut kusuma wijaya (Fakultas Ekonomi Universitas Islam Al-Azhar, 2018)
Banks play an important role in the economy of a country and all community activities are always in contact with banks. The bank as a very important institution has a role as the creation and circulation of money, supporting business activities and other financial activities. As the backbone of the economy the bank must have excellent financial performance. One of the financial performance is seen from the financial statements, namely the balance sheet and profit and loss. One indicator to assess financial performance is by camel analysis. In camel analysis that is assessing the performance of indicators of capital, assets, earnings management and liquidity. This study aims to analyze the financial performance of PT Bank BPD NTB for the period 2012-2017. The research method used is quantitative descriptive with camel analysis namely (CAR, NPL, NPM, ROA and LDR). The type of financial data used is Commercial Bank Reports obtained from the Financial Services Authority website. The results of the analysis show that PT Bank BPD NTB is categorized as healthy. As a bank with a healthy category, PT Bank BPD NTB should increase the provision of MSME credit (Micro, Small and Medium Enterprises) because the provision of credit to this sektor provides greater profits and increases the portion of third party funding sources in the form of savings and checking accounts. At least this will increase the company's profit.